The use of faecal microbiota transplant as treatment for recurrent or refractory Clostridium difficile infection and other potential indications: joint British Society of Gastroenterology (BSG) and Healthcare Infection Society (HIS) guidelines. Issue 11 (28th August 2018) - Mullish, Benjamin H; Quraishi, Mohammed Nabil; Segal, Jonathan P; McCune, Victoria L; Baxter, Melissa; Marsden, Gemma L; Moore, David J; Colville, Alaric; Bhala, Neeraj; Iqbal, Tariq H; Settle, Christopher; Kontkowski, Graziella; et al.
Abstract : Interest in the therapeutic potential of faecal microbiota transplant (FMT) has been increasing globally in recent years, particularly as a result of randomised studies in which it has been used as an intervention. The main focus of these studies has been the treatment of recurrent or refractory Clostridium difficile infection (CDI), but there is also an emerging evidence base regarding potential applications in non-CDI settings. The key clinical stakeholders for the provision and governance of FMT services in the UK have tended to be in two major specialty areas: gastroenterology and microbiology/infectious diseases. While the National Institute for Health and Care Excellence (NICE) guidance (2014) for use of FMT for recurrent or refractory CDI has become accepted in the UK, clear evidence-based UK guidelines for FMT have been lacking. This resulted in discussions between the British Society of Gastroenterology (BSG) and Healthcare Infection Society (HIS), and a joint BSG/HIS FMT working group was established. This guideline document is the culmination of that joint dialogue.